Wina Sentosa Bottled Water Distribution System Using Web-Based Distribution Requirement Planning and Trend Moment Algorithms - Uswary, Jonathan Albert; Ngemba, Hajra Rasmita; Hendra, Syaiful; Kasim, Anita Ahmad (Advance Sustainable Science, Engineering and Technology, 2024)
This research focuses on the problem of PT Anugrah Wina Sentosa, which is a producer of bottled drinking water in Central Sulawesi. The company faces challenges in organizing and improving the efficiency of the distribution of bottled drinking water products. Problems include distribution management that has not been optimized and distribution arrangements at various outlets that have not been mapped. Based on this problem, researcher develop a web-based distribution system with the Distribution Requirement Planning (DRP) algorithm and Trend Moment Algorithm to see the results of sales and distribution predictions. The designed application can carry out data processing, Distribution Requirement Planning processes, Trend moment processes, MAPE calculations, and sales predictions. The application development method uses the Waterfall method. The test results show that the system can manage input, edit, and delete data and run DRP calculations as a whole or per outlet. With an error value of 1.71%, the trend moment forecasting system proved to be very accurate in forecasting sales of drinking water products. Thus, the implementation of a web-based distribution system can improve production efficiency and facilitate stock management and distribution management at PT Anugrah Wina Sentosa. This research has several limitations that need to be considered, namely limited scope, limited data, limited generalization, limited affordability, and limited time.